Extraction and elucidation of chemical constituents from the roots of Derris Elliptic A / Tengku Muzzabfarrullah Tengku Sham - Tengku Sham, Tengku Muzzabfarrullah (Faculty of Applied Sciences, 2008)
The chemical compounds form the roots of Derris elliptica were extracted and isolated by various chromatography methods. The isolated compounds were elucidated by the spectroscopic methods. Extractions of the roots of Derris elliptica (300g) were done by macerated in the chloroform. The extraction yield crude extract 8.74g (0.03 % w/w) were isolated using the chromatography methods. Vacuum liquid chromatography (VLC) and Radial chromatography (RC) were used to isolate the crude extract. Thin layer chromatography (TLC) was used to identify the pure compounds. The isolated crude produce two compound were produce labeled DEI (16.7mg) and DE2 (14.1mg). The pure compound were elucidated by the spectroscopic method; Nuclear Magnetic Resonance (NMR), Gas Chromatography - Mass Spectrometry (GC-MS), UV spectroscopy and Fourier Transform Infrared (FTIR). From the comparison of the spectrums with the literature reviews, the compounds were identified. Compound DEI known as rotenone and compound DE2 known as 2\-hydroxy-r,2'-dihydrorotenone.